ANALISIS STRATEGI PEMASARAN PADA PT JAPFA COMFEED INDONESIA TBK, UNIT PADANG - Tia Indriani; Rose Rahmidani (Universitas Negeri Padang, 2018)
This research was attempted to formulate the strategy of marketing to increase volume of animal feed at PT Japfa Comfeed Indonesia Tbk, Unit Padang. The research did by using case study method at PT Japfa Comfeed Indonesia Tbk, Unit Padang in collecting data. The data has collected was analyzed on descriptive by using matrix strenghts, weaknesses, opportunities, and threats (SWOT). To get the strategy the researcher have Three stages. The Were 1 (input stage) consist of EFE (external factor evaluation) from Environment, 2 (stage matching) that have result alternative strategy, 3 (stage result) based on SWOT, the best strategy to increase the volume of animal feed sales at PT Japfa Comfeed Indonesia Tbk, Unit Padang was an intensive strategy and integrationstrategy. Keywords: Marketing Strategy, SWOT Analysis,EFE Matrix, IFE-Matrix